IFN‐γ directly inhibits murine B‐cell precursor leukemia‐initiating cell proliferation early in life. Issue 5 (11th April 2017) - Fidanza, Mario; Seif, Alix E.; Jo, Sumin; Kariminia, Amina; Rolf, Nina; Sly, Laura M.; Grupp, Stephan A.; Reid, Gregor S. D.
Abstract : The immune system is thought to modulate childhood acute leukemia progression but the mechanisms are unknown. Here, we show that basal IFN‐γlevels exert SOCS‐1‐mediated control over pre‐leukemia expansion and delay leukemia onset in mice. This finding provides the first demonstration that the neonatal immune environment can influence acute leukemia. Abstract : The early‐life immune environment has been implicated as a modulator of acute lymphoblastic leukemia (ALL) development in children, with infection being associated with significant changes in ALL risk. Furthermore, polymorphisms in several cytokine genes, including IL‐10 and IFN‐γ, are associated with leukemia development. However, the mechanisms and timing of these influences remain unknown. Here, we use the Eμ‐ret transgenic mouse model of B‐cell precursor ALL to assess the influence of IFN‐γ on the early‐life burden of leukemia‐initiating cells. The absence of IFN‐γ activity resulted in greater numbers of leukemia‐initiating cells early in life and was associated with accelerated leukemia onset. The leukemia‐initiating cells from IFN‐γ‐knockout mice had reduced suppressor of cytokine signaling (SOCS‐1) expression, were significantly more sensitive to IFN‐γ, and exhibited more rapid expansion in vivo than their wild‐type counterparts. However, sensitivity to this inhibitory pathway was lost in fully transformed IFN‐γ‐knockout leukemia cells. These results demonstrate that the influence of IFN‐γ on ALL progression may not be mediated by selection of nascent transformed cells but rather through a general SOCS‐mediated reduction in B‐cell precursor proliferation. Thus, while cytokine levels may influence leukemia at multiple points during disease progression, our study indicates a significant early influence of basal, infection‐independent cytokine production on leukemogenesis.